Prognostic Utility of FBLN2 Expression in Patients With Urothelial Carcinoma - Li, Wei-Ming; Chan, Ti-Chun; Huang, Steven Kuan-Hua; Wu, Wen-Jeng; Ke, Hung-Lung; Liang, Peir-In; Wei, Yu-Ching; Shiue, Yow-Ling; Li, Chien-Feng (Frontiers in Oncology, 2020)
Background: Abnormal extracellular matrix (ECM) remodeling plays an essential role in urothelial carcinoma (UC) invasiveness and metastasis. Focusing on the ECM structural constituent (GO: 0005201), we recognized a significant upregulation of the fibulin 2 gene (FBLN2) during UC progression in a published UC transcriptome (GSE31684). Thus, we aimed to investigate the roles of FBLN2 expression and its prognostic value in upper urinary tract UC (UTUC) and urinary bladder UC (UBUC) in our large, well-characterized cohort. Patients and Methods: Clinicopathological data and formalin-fixed paraffin-embedded UC tissues were analyzed retrospectively. We determined FBLN2 expression using immunohistochemical staining assessed by H-scores. FBLN2 expression correlated with clinicopathological features and patient outcomes, including metastasis-free survival (MFS) and disease-specific survival (DSS). Statistical analyses were performed using Pearson’s chi-square test, Kaplan-Meier estimates of DSS and MFS, and the Cox proportional hazards model. We used Ingenuity Pathway Analysis (IPA) to clarify the functional significance of dysregulated FBLN2 in UC. Results: Data from 295 UBUC and 340 UTUC patients were available for the final evaluation. Pearson’s chi-square test showed that high FBLN2immunoexpression significantly correlated with adverse pathologic variables, such as advanced pathologic tumor stage, high histological grade, perineural invasion, vascular invasion, lymph node metastasis, and increased mitotic rate (all p<0.05). Kaplan-Meier analysis demonstrated associations of high FBLN2 expression with worse DSS (p<0.001) and MFS (p<0.001). Furthermore, multivariate analysis identified high FBLN2 expression as an independent predictive risk factor for DSS (hazard ratio [HR] in UBUC, 2.306, p=0.014; in UTUC, 2.561, p=0.012) and MFS (HR in UBUC, 2.493, p=0.001; in UTUC, 2.837, p=0.001). IPA demonstrated that multiple signaling pathways were enriched, including the oxidative phosphorylation, mitochondrial dysfunction, and regulation of the epithelial-mesenchymal transition pathways. Conclusion: High FBLN2 expression was associated with adverse pathologic features and worse oncological outcomes and may serve as a prognostic biomarker for UC.